(untitled) (Texas Journal of Multidisciplinary Studies, 2021)
The perfect study of the rules and units of foreign language grammar, which are unfamiliar to Uzbeks, is a skill that arises from a very diligent practice. z compounds, describing their types and similarities and differences in the two languages. The grammatical material on infinitive phrases is widely available in the field of German language practice and theory. There are materials on this in all grammar textbooks and manuals. Even in large-volume German-Russian and German-Uzbek dictionaries, there are cases when some rules for word formation are emphasized